Factors influencing the selection of a university among first-year students – A case of a university of technology in South Africa - Funeka, L. P.; Govender, N.; Govender, V. (South African Journal of Higher Education, 2024)
The social and political history of South Africa yielded massive transformation in the higher education landscape, including access to education and the merger of universities. Despite the many successes of transformation, it brought with it challenges such as increasing participation, student retention, throughput, and graduation rates; changes in government funding models; declining student subsidies and providing quality education with limited resources. The South African higher education sector is multi-faceted, and students have a wide range of higher education options. This study explored factors influencing decision-making of first-year students when selecting a university. Data was collected from first-year students and employees at a University of Technology. Through in-depth interviews and focus group discussions, the researchers analysed the complex factors that guide students’ decision-making when selecting a university. The findings revealed that factors significantly influencing decision-making on university selection are, the reputation and quality of university programmes offered, response time and support provided by staff; location; and infrastructure and facilities. This research is significant in that it will assist higher education institutions, particularly marketing and communications departments to be more responsive to students’ needs by shifting toward active engagement in its marketing and recruitment approaches to attract, retain, and satisfy students.